ANALISIS PENGARUH PROFITABILITAS DAN GROWTH TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Listiyowati, Listiyowati (JAB (Jurnal Akuntansi & Bisnis), 2020)
Pharmaceutical companies are becoming Asian emerging markets in the fulfillment of BPJS / JKN service medicines which have an impact on the company's sales level. However, in the pharmaceutical sector there is a gap between companies that have a large and small scale, so that the achievement of profits is not evenly distributed, and this has an impact on the company's stock price. This study aims to determine the effect of profitability and growth on stock prices with capital structure as an intervening variable. The population in this study were 40 pharmaceutical companies listed on the IDX in 2016-2019. By using purposive sampling method, it was obtained a sample of 32 company data. The analysis technique uses the classical assumption test and path analysis. The research result states that profitability, growth and capital structure have no effect on share prices partially. However, changing the capital structure as an intervening variable results in profitability and growth being able to have an influence on stock prices.Â Keywords: Stock Price, Profitability, Growth, Capital Structure